The positive and the negative: assessing critical realism and social constructionism as post-positivist approaches to empirical research in the social sciences - Cruickshank, J (International Migration Institute, 2011)
The argument developed in this paper holds that critical realism is stronger than many other forms of post-positivism but that it is itself open to criticism. While critical realists are polemical about positivism they do share with positivism the concern positively to develop knowledge. This stands in contrast to social constructionism which embraces relativism and scepticism in an attempt to delegitimize knowledge claims by exposing them as symptoms of underlying discursive power relations. For critical realists we need to defend knowledge from relativist and sceptical challenges while seeking to avoid the empiricist theory of knowledge that underpinned positivism. To do this critical realists turn from empiricism – and epistemology more generally – to ontology, and argue that the natural and social sciences need to be based on a coherent definition of reality. As regards the social sciences, critical realists argue that a meta-theory which defines social reality in terms of agents interacting with structural emergent properties is required to underpin empirical research. This non-positivist emphasis on generating knowledge about causal processes in society is stronger than social constructionism, which cannot move beyond the purely negative position of scepticism. However, we may consider problem-solving challenges to critical realism. These focus on the need for conceptual revision in contrast to the critical realist argument that the meta-theory of structure and agency is the condition of possibility of a mature social science.